2010
DOI: 10.1590/s0102-05362010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo orgânico sequencial de hortaliças com dois sistemas de irrigação e duas coberturas de solo

Abstract: Com o aumento da demanda por produtos ecologicamente corretos tornaram-se necessários estudos de novas tecnologias para inseri-las no método de cultivo orgânico para que se tenha um crescimento sustentável da atividade. Neste trabalho avaliou-se o desempenho de cultivares e híbridos de hortaliças cultivados seqüencialmente no método orgânico, em diferentes ambientes. O delineamento experimental foi de parcelas sub-subdivididas com 3 repetições, resultando em 24 unidades experimentais. Foram estudados dois méto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
6
0
6
Order By: Relevance
“…were not significantly affected by the treatments (Table 1). These results are in agreement with Branco et al (2010) and Marouelli et al (2011a), who also found no variation in the productivity of the organic tomato whether irrigated by drip or sprinkler. This differs however from studies conducted in conventional production systems, where the yield of the tomato irrigated by drip is typically greater than when irrigated by sprinkler (HANSON, MAY, 2004;MAROUELLI et al, 2003).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…were not significantly affected by the treatments (Table 1). These results are in agreement with Branco et al (2010) and Marouelli et al (2011a), who also found no variation in the productivity of the organic tomato whether irrigated by drip or sprinkler. This differs however from studies conducted in conventional production systems, where the yield of the tomato irrigated by drip is typically greater than when irrigated by sprinkler (HANSON, MAY, 2004;MAROUELLI et al, 2003).…”
Section: Resultssupporting
confidence: 92%
“…The search for healthy foods which are free from contamination by pesticides has been increasing, with the rate of growth of the organic sector in Brazil reaching 30% per year (BRANCO et al, 2010). Among the vegetables produced under organic systems, the tomato (Solanum lycopersicum L.) is one of the most sought after by Brazilian consumers, as its production under conventional systems demands the intensive use of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Com o aumento da demanda por produtos ecologicamente corretos, tornaram-se necessários estudos de novas tecnologias para inseri-los no método de cultivo orgânico, para que se tenha um crescimento sustentável da atividade (BRANCO et al, 2010). Na agricultura orgânica, grande parte da energia utilizada provém de microrganismos, plantas, trabalho humano, animal e estercos, denominados aporte cultural biológico (GLIESSMAN, 2000).…”
Section: Introductionunclassified
“…Essa massa fresca por planta de 239,59 g é semelhante à massa fresca de alface observada em outros trabalhos desenvolvidos na região (CARVALHO et al, 2005;FERREIRA et al, 2009;LÊDO;SOUZA;SILVA, 2000), enquanto o cultivo em regiões de clima ameno, como em Seropédica-RJ (OLIVEIRA et al, 2006) e São Roque-SP (BRANCO et al, 2010), proporciona plantas com maior massa fresca, 348 g planta -1 e 696,26 g planta -1…”
Section: Methodsunclassified
“…A cobertura do solo com plásticos proporciona maior controle de plantas espontâneas, menor evaporação da água do solo, economia de água de irrigação (FERREIRA et al, 2006BRANCO et al, 2010) menor amplitude térmica do solo e maior rentabilidade econômica em comparação ao solo descoberto, tanto em cultivo protegido como a céu aberto (ARAÚJO NETO et al, 2009).…”
Section: Introductionunclassified